Flower, fruit phenology and flower traits inCordia boissieri(Boraginaceae) from northeastern Mexico - Martínez Adriano, Cristian Adrián; Jurado, Enrique; Flores, Joel; González Rodríguez, Humberto; Cuéllar Rodríguez, Luis Gerardo (2016)
We characterized variations in Cordia boissieri flowers and established if these variations occur between plants or between flowering events. Flowering and fruiting was measured for 256 plants. A GLM test was used to determine the relationship between flowering and fruit set processes and rainfall. We performed measurements of floral traits to detect variations within the population and between flowering events. The position of the anthers with respect to the ovary was determined in 1,500 flowers. Three out of four flowering events of >80% C. boissieri plants occurred after rainfall events. Only one flowering event occurred in a drought. Most plants flowered at least twice a year. The overlapping of flowering and fruiting only occurred after rainfall. Anthesis lasted threeto-five days, and there were two flower morphs. Half of the plants had longistylus and half had brevistylus flowers. Anacahuita flower in our study had 1–4 styles; 2–9 stamens; 6.5–41.5 mm long corolla; sepals from 4.5–29.5 mm in length; a total length from 15.5–59 mm; a corolla diameter from 10.5–77 mm. The nectar guide had a diameter from 5–30.5 mm; 4–9 lobes; and 5 distinguishable nectar guide colors. The highest variation of phenotypic expression was observed between plants.